2017
DOI: 10.1111/ajt.13886
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Outcomes of Extended Criteria Donor Kidneys by Subtype: Subgroup Analysis of BENEFIT-EXT at 7 Years After Transplant

Abstract: The phase III Belatacept Evaluation of Nephroprotection and Efficacy as First‐Line Immunosuppression Trial–Extended Criteria Donors Trial (BENEFIT‐EXT) study compared more or less intensive belatacept‐based immunosuppression with cyclosporine (CsA)–based immunosuppression in recipients of extended criteria donor kidneys. In this post hoc analysis, patient outcomes were assessed according to donor kidney subtype. In total, 68.9% of patients received an expanded criteria donor kidney (United Network for Organ Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 34 publications
(56 reference statements)
1
12
1
2
Order By: Relevance
“…Concerning safety and in contrast to Florman et al [13], we found that Belatacept treatment was associated with an increased incidence of severe infections in the univariate Cox regression. The most obvious differences were higher event rates of diarrhoea, urinary tract infection and sepsis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Concerning safety and in contrast to Florman et al [13], we found that Belatacept treatment was associated with an increased incidence of severe infections in the univariate Cox regression. The most obvious differences were higher event rates of diarrhoea, urinary tract infection and sepsis.…”
Section: Discussioncontrasting
confidence: 99%
“…eGFR improved with Belatacept treatment, but slightly decreased during CNI therapy and, in the multivariate analysis, Belatacept treatment was the only significant factor for the improvement of ΔeGFR. This is in line with the BENEFIT and BENEFIT-EXT studies, which also demonstrated an increase of GFR over a follow-up of seven years [12,13,14]. However, the CNI comparator cohort consisted of cyclosporine A-treated patients only, whereas our group was mainly treated with tacrolimus (68% of patients).…”
Section: Discussionsupporting
confidence: 87%
“…During phase II and III trials in KTRs, there were safety concerns regarding belatacept because of an observed increased incidence of PTLD . A total of 16 patients receiving belatacept developed PTLD, and seven of these cases had CNS involvement . Given these concerns, the U.S. Food and Drug Administration (FDA) approval carries a boxed warning for the risk of PTLD, especially in EBV‐seronegative patients.…”
Section: Immunosurveillance and Immunosuppressionmentioning
confidence: 99%
“…5 Sin embargo, los esquemas a base de belatacept ofrecen mejor función renal a largo plazo y mejor sobrevida del injerto a pesar de que pudieran tener mayor tasa de rechazo en el primer año. 6 En los últimos años se ha demostrado que cualquier esquema con uso de inhibidores mTOR está asociado a mayor mortalidad y menor sobrevida del injerto, por lo que sólo se recomiendan en casos muy especiales. 7 Respecto al manejo de inmunosupresión de mantenimiento durante la infección por SARS-CoV-2 ha sido muy heterogéneo, se realiza principalmente basado en opinión de expertos y traslapando la conducta que se toma frente a infecciones sistémicas graves.…”
Section: Terapia De Mantenimientounclassified